Thought and Action in Foreign Policy - BOHAM. author. aut Link
VII, 357 p.
Keywords: This volume is the product of the Conference on Cognitive Process Models of Foreign Policy Decision-Making which was held in London at the Richardson Institute for Conflict and Peace Research from March 17-24, 1973. We would like to thank Michael Nicholson, Director of the Richardson Institute, for acting as the host of the Conference. Support for the Conference and the preparation of the Conference papers for publication was provided by the Mathematical Social Sciences Board (MSSB). The MSSB is funded by aNational Science Foundation grant which is administered by the Center for Advanced Study in the Behavioral Sciences as the primary grantee. We are grateful to Hayward Alker, Jr. and William H. Riker of the MSSB for their help and encouragement. The graph shown on the cover is a cognitive map representation of the output from our computer simulation of foreign pOlicy decision-making. We would like to thank Robert Axelrod and Gary Raffel of the University of Michigan for generating the graph. PART I INTRODUCTION 1 CHAPTER 1 THOUGHT AND ACTION IN FOREIGN POLICY G. MATTHEW BONHAM The American University MICHAEL J. SHAPIRO University of Hawaii Introduction The papers assembled here constitute, and to some extent represent, widely disparate views of foreign policy thinking and decision-making. As is the case with almost any collective enterprise, it is possible to suggest some noteworthy resemblances among the contributions to this volume and to indicate grounds for distinguishing them from other "approaches.